Perubahan Budaya: Dampak Westernisasi Melalui Media Sosial pada Anak Muda (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Technology that continues to develop becomes a medium of access to see the outside world. Young people as the backbone of the future began to follow the flow of the times and technology. The presence of a lot of content on social media makes young people start consuming foreign cultures, this cannot be separated from the influence of globalization, a reality that has real consequences on how people and institutions around the world run. They believe that local countries and cultures will be lost to global culture and economy. It is undeniable that the influence of globalization on cultural diffusion is increasingly visible with the development of information technology, so that cultural diffusion no longer has to go through migration but can take place through internet access that can be connected to the world.This research uses qualitative methods by looking for sources of information with a descriptive literature study approach. Social media has become the main channel that facilitates the transfer of Western values such as the concepts of individualism, consumerism, and views related to freedom of expression. Nowadays young people tend to forget local culture as an inherent identity and follow the flow of westernization which is considered more modern and more advanced than local culture which is considered traditional and ancient, this tendency is because young people follow more prestige in the development of the times without thinking about the consequences it causes.